Work Motivation as a Strategic Driver of Employee Performance in Public Organizations - Ade Setiadi (International Journal of Science Education and Cultural Studies, 2024)
Employee performance is a major factor in determining the effectiveness of an organization, especially in the public sector where the quality of service is determined by human resources. This study examines the effect of work motivation on employee performance at the Department of Education and Culture of Indramayu Regency. A quantitative approach was used, and a census of 54 employees was conducted. Data were collected through a structured questionnaire based on Maslow’s hierarchy of needs and analyzed using descriptive statistics and path analysis. The results show that employees perceive both work motivation and performance at a good level. Work motivation had a positive and significant effect on employee performance with 89.4% of its variance (R 2 = 0.894). All motivational dimensions contributed positively indicating the importance of fulfilling physiological, safety, social, esteem and self-actualization needs of employees. The study provides empirical evidence for the strategic role of work motivation in improving employee performance and offers practical implications for motivation based human resource management in local government organizations